RESEARCH ON THE EVOLUTION OF FRUIT FARMS IN ROMANIA, IN THE PERIOD 2005-2016 - Claudiu Stelică COADĂ; Camelia Maria PROCOP; Valentina Constanța TUDOR (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The trade balance in the fruit sector of Romania shows significant deficits, which are accentuated from one year to another. In order to identify the causes leading to these issues, the main source of the problem, namely fruit farms, was analyzed. The aim of the paper is to identify the causes, based on which, the best solution for this problem is the association of fruit growers. In this paper, the fruit farms were analyzed in the period 2005-2016 (being the most recent data available), depending on the legal form, physical size and economic size, using quantitative and qualitative methods of data processing.